2014
DOI: 10.1007/s00415-014-7462-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage risk with the new oral anticoagulants: a systematic review and meta-analysis

Abstract: The new oral anticoagulants/non-vitamin K antagonists oral anticoagulants (NOACs) have recently reached the market and less is known about their safety in comparison to their efficacy. Therefore, we aimed to evaluate intracranial hemorrhage (ICH) risk with NOACs, the most feared adverse event of anticoagulation treatment. This is a systematic review and meta-analysis of phase III randomized controlled trials (RCTs) comparing NOACs versus any control and reporting ICH events. Studies were searched through Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 42 publications
1
51
0
5
Order By: Relevance
“…1,2 The agents currently available include the direct thrombin inhibitor dabigatran and the direct factor Xa (FXa) inhibitors rivaroxaban, apixaban, and edoxaban. In general, observations from clinical trials and subsequent meta-analyses have suggested similar or lower major bleeding rates with the DOACs when compared with warfarin, [3][4][5][6][7] particularly for central nervous system (CNS) bleeding events. 8 One exception may be gastrointestinal bleeding events, as higher rates have been observed in patients receiving DOACs when com- …”
Section: Discussionmentioning
confidence: 99%
“…1,2 The agents currently available include the direct thrombin inhibitor dabigatran and the direct factor Xa (FXa) inhibitors rivaroxaban, apixaban, and edoxaban. In general, observations from clinical trials and subsequent meta-analyses have suggested similar or lower major bleeding rates with the DOACs when compared with warfarin, [3][4][5][6][7] particularly for central nervous system (CNS) bleeding events. 8 One exception may be gastrointestinal bleeding events, as higher rates have been observed in patients receiving DOACs when com- …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to VKAs, NOACs have a lower risk of major bleeding events such as intracranial hemorrhage [4], a faster onset of action, a predictable dose-response relationship, and does not require frequent anticoagulation intensity evaluation, similar to INR testing in patients treated with VKA [5]. Different from ximelagatran (an oral anti-IIa inhibitor withdrawn due to the high risk of liver injury), recent NOACs did not show increased risk of drug-induced liver injury [6].…”
Section: Introductionmentioning
confidence: 99%
“…Последующие мета-анализы показали, что группа НОАК характеризуется пониженным риском развития больших кровотечений по сравнению с АВК, в особенности при терапии ВТЭО [19]. Аналогичное преимущество было продемонстрировано в отношении риска развития внутричерепных кровоизлия-ний и летальных кровотечений [20,21].…”
Section: Discussionunclassified